Exchange rate volatility and export performance: A cointegrated VAR approach - Pål Boug; Andreas Fagereng (Statistics Norway, Research Department, 2007)
During the last decades Norwegian exporters have - despite various forms of exchange rate targeting - faced a rather volatile exchange rate which may have influenced their behaviour. Recently, the shift to inflation targeting and a freely floating exchange rate has brought about an even more volatile exchange rate. We examine the causal link between export performance and exchange rate volatility across different monetary policy regimes within the cointegrated VAR framework using the implied conditional variance from a GARCH model as a measure of volatility. Although treating the volatility measure as either a stationary or a non-stationary variable in the VAR, we are not able to find any evidence suggesting that export performance has been significantly affected by exchange rate uncertainty. We find, however, that volatility changes proxied by blip dummies related to the monetary policy change from a fixed to a managed floating exchange rate and the Asian financial crises during the 1990s enter significantly in a dynamic model for export growth - in which the level of relative prices and world market demand together with the level of exports constitute a significant cointegration relationship. A forecasting exercise on the dynamic model rejects the hypothesis that increased exchange rate volatility in the wake of inflation targeting in the monetary policy has had a significant impact on export performance.
Keywords: C51; C52; F14; F17; 330; Exports; exchange rate volatility; GARCH; CVAR; forecasting